A HYBRID KB-AHP-GAP ANALYSIS FOR THE PERFORMANCE MEASUREMENT SYSTEM IN A MANUFACTURING ENVIRONMENT. PART 2: THE DETAILED PMS SYSTEM - Wibisono, Dermawan (Jurnal Manajemen Teknologi, 2003)
This paper presents on designing and managing performance of a manufacturing unit from the corporate level to the shop floor level. A Hybrid Knowledge Based (KB) Analytic Hierarchy Process (AHP) Gauging Absence of Pre-requisite (GAP) analysis of Performance Measurement System (PMS) Model is developed that considers five levels of company performance: Business Perspective, Customers Perspective, Manufacturing Competitive Priorities Perspective, Internal Process Perspective, and Resources & Method Availability Perspective. The research validation was confined to four industry sectors: aircraft component manufacturing, electronics manufacturing, computer and office equipment manufacturing and telecommunication product manufacturing. The results of the validation exercise indicate that the present Hybrid PMS Model is suitable decision-making tool to assist the practitioners of PMS and provides consistent and detailed results.Â Keywords:Â Performance Measurement System, Knowledge Based, Analytic Hierarchy Process, GAP Analysis, Manufacturing